New Structured Materials in the Study of the Mechanobiological Processes Related to the Heart Failure - González Lana, Sandra; Belaza, Andrés; Vigueras, Alan; Virumbrales, María; Llamazares, Guillermo; Asín, Laura; de la Fuente, Jesús M.; Medel, Francisco; Doweidar, Mohamed H.; Oliván, Sara; Fernández, Luis F.; Doblaré, Manuel; et al. (Jornada de Jóvenes Investigadores del I3A, 2017)
Cardiovascular diseases are the number one of death globally. According to the World Health organization 17.7 million people died from cardiovascular diseases in 2015, representing 31% of all global deaths. In these diseases the cardiac homeostasis is disrupted by a non-appropriate myocardium remodelling. The cardiac extracellular matrix (ECM) provides not only the biochemical environment but also a natural scaffold surrounding and connecting cardiac cells and distributing mechanical forces throughout the organ. Thus, the properties of the ECM are essential for the maintenance of the functional myocardium. Alterations in cardiac ECM structure associated with heart failure influence cell-matrix and cell-cell adhesions modifying cell shape and mechanotransduction. The need to understand the cardiac ECM remodelling mechanisms that allow us to identify new therapeutic targets lead us to create biomimetic scaffolds which emulate the structure, topography, mechanics and chemical composition of ECM. Here, we present the development of modulable materials for the manufacturing, by using photopolymerizable materials, of structured hydrogels with myocardium properties of stiffness and elastic modulus in physiological and pathological conditions.